2010
DOI: 10.1189/jlb.0910506
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3+IL-17+ T cells promote development of cancer-initiating cells in colorectal cancer

Abstract: The pathogenesis of CRC remains to be further understood. This study was designed to elucidate the role of Foxp3+IL-17+ T cells in the pathogenesis of CRC. Surgically removed CRC tissue was collected from 12 patients with CRC. The frequency and cytokine profile of Foxp3+IL-17+ T cells in CRC were examined by flow cytometry. Chemokine CXCL11 was examined in CRC tissue by Western blotting. Treg chemotaxis was examined in a transwell system. The effect of Foxp3+IL-17+ T cells on induction of cancer-initiating cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 28 publications
4
109
0
2
Order By: Relevance
“…In tumor cells, expression of TNFa might be upregulated in a Cirp-independent manner. IL23 and IL17 inhibit antitumor immunity and promote tumorigenesis (6)(7)(8). Expression of IL23 and IL17 was decreased in Cirp À/À tumors and nontumor colons compared with WT counterparts (Fig.…”
Section: And E Effect Of Cirp On Gene Expression In Colonic Laminamentioning
confidence: 99%
See 1 more Smart Citation
“…In tumor cells, expression of TNFa might be upregulated in a Cirp-independent manner. IL23 and IL17 inhibit antitumor immunity and promote tumorigenesis (6)(7)(8). Expression of IL23 and IL17 was decreased in Cirp À/À tumors and nontumor colons compared with WT counterparts (Fig.…”
Section: And E Effect Of Cirp On Gene Expression In Colonic Laminamentioning
confidence: 99%
“…IL23/IL17 signaling enhances the immunosuppressive activity of regulatory T cells and reduces CD8 þ cells in tumor, leading to enhanced tumor initiation and promotion (6,7). Recently, a study has suggested that colorectal cancer tissue-derived Foxp3 þ IL17 þ cells have the capacity to induce cancer-initiating cells in vitro (8). The most conspicuous link between inflammation and colon cancer is seen in patients with IBD (9), and development of colorectal cancer is one of the most serious complications of IBD, which is also referred to as colitis-associated cancer (CAC; ref.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism underlying these effects can be mimicked by induction of the hypoxia-inducible factor (HIF), which acts to regulate cellular processes, including glucose metabolism, angiogenesis, cell proliferation, and tissue remodeling (7). Recent reports indicate that hypoxia facilitates the generation of Tregs in tumor tissue (8) or strengthens the function of Tregs (9) in tumors, but the underlying mechanism is incompletely understood.…”
Section: Cd8mentioning
confidence: 99%
“…However, an increase of Tregs is also attributed to the expression of VEGF (32)(33). Intriguingly, recent reports demonstrate that interleukin 17-producing Tregs drive cells to become cancer-initiating cells in colorectal cancer (34). Finally, Tregs indirectly interact with CSCs partially driving the differentiation of tumourassociated macrophages that release TGFβ (35).…”
Section: Discussionmentioning
confidence: 98%